ENHANCING GRAMMAR TEACHING IN AN INDONESIAN SENIOR HIGH SCHOOL THROUGH THE USE OF GRAMMAR WHEEL - Syakira, Syafa Azmi; Priyana, Joko; Lestari, Aryanti Eka; Dewi, Ifti Luthviana; Pujiasih, Erna (University of Kuningan, 2024)
Attaining proficiency in grammar is crucial for students as it serves as the foundation for language use. However, many individuals shy away from learning it, perceiving it as a daunting and challenging task. This research is aimed at enhancing grammar teaching by applying Grammar Wheel. It focuses on the active and passive voice mastery of three forms of tenses including simple past tense, past continuous tense, and past perfect tense. Conducted in one of the public Senior High Schools in Indonesia, this study was participated by 35 students and an English teacher. Having troubles in comprehending grammar, the teacher needed media and activities to deliver the grammar materials interestingly. Two cycles of Classroom Action Research (CAR) were implemented. The data were collected using observation sheets, field notes, video recordings, interview guidelines, and exercise sheets. The analysis was carried out qualitatively following the steps proposed by Cresswell (2012). The results revealed that language teaching had been successfully improved and students were more motivated to engage in the learning process being in a comfortable and supportive learning environment. Furthermore, learners’ knowledge in mastering the three types of tenses increased significantly as evidenced by their writing. Hence, the Grammar Wheel has proven to be an effective tool for teaching grammar in the classroom.